The influence of working hours on job performance CV. Trimitra Binatama Oetete Consultant Kupang City - Benu, Yessi; Wisang, Theresia (CV. Jala Berkat Abadi, 2024)
This study was conducted to determine the Effect of Working Hours on Employee Performance CV. Trimitra Binatama Consultant Oetete Kupang City, The formulation of the problem in this study is whether there is an Effect of Working Hours on Employee Performance CV. Trimitra Binatama Consultant Oetete Kupang City, The purpose of this study was to determine the effect of working hours on employee performance CV. Trimitra Binatama Consultant Oetete Kupang City. This study uses quantitative research methods with data collection techniques, namely questionnaires, interviews, observation and documentation, the population in this study amounted to 34 respondents using saturated sampling techniques where all populations were sampled. All data in this study were collected through questionnaires, interviews, observations and documentation, then analyzed by validity, reliability, simple linear regression normality test and T test. Data processing uses SPSS 25 software for windows. The results showed that there was a significant positive effect of working hours on employee performance at CV. Trimitra Binatama Consultant and. This research supports the importance of managing working hours in an effort to improve employee performance. The variable working hours (X) explains that employee performance (Y) regression model shows that only about 24.2% of the employee performance variable can be explained by working hours, the identified relationship remains significant and relevant.